2022
DOI: 10.2196/35307
|View full text |Cite
|
Sign up to set email alerts
|

Predicting 30-Day Readmission Risk for Patients With Chronic Obstructive Pulmonary Disease Through a Federated Machine Learning Architecture on Findable, Accessible, Interoperable, and Reusable (FAIR) Data: Development and Validation Study

Abstract: Background Owing to the nature of health data, their sharing and reuse for research are limited by legal, technical, and ethical implications. In this sense, to address that challenge and facilitate and promote the discovery of scientific knowledge, the Findable, Accessible, Interoperable, and Reusable (FAIR) principles help organizations to share research data in a secure, appropriate, and useful way for other researchers. Objective The objective of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…The clinical assessment concluded that from 100 recruited patients, the prediction was correct in 87% of cases (that is, in real-life, the patient was readmitted and the algorithm predicted that there was early 30-days hospital readmission risk; or the patient was not readmitted and the algorithm predicted that there was not early 30-days hospital readmission risk). The results and main findings of the second use case are been published (Open Access paper accepted and is currently in production) 13 .…”
Section: Resultsmentioning
confidence: 99%
“…The clinical assessment concluded that from 100 recruited patients, the prediction was correct in 87% of cases (that is, in real-life, the patient was readmitted and the algorithm predicted that there was early 30-days hospital readmission risk; or the patient was not readmitted and the algorithm predicted that there was not early 30-days hospital readmission risk). The results and main findings of the second use case are been published (Open Access paper accepted and is currently in production) 13 .…”
Section: Resultsmentioning
confidence: 99%
“…Throughout this study, we considered 250 texts focused on OFD (after title screening) that represented a diversity of research areas and aims but found that any claims of societal impact were speculative rather than based on observed and documented usage. For example, possible impacts included potential privacy violations [227,228], improvements in health research [229][230][231], or better monitoring of SDGs [232], yet evidence to back these claims was not presented.…”
Section: Discussionmentioning
confidence: 99%
“…The FAIR principles aim to ensure that data is shared in a way that enables and enhances the reuse of information by humans and machines. Numerous researchers have analyzed the advantages of applying FAIR principles in the field of health [ 4 ] and especially in the research of patients with chronic diseases [ 5 , 6 ]. In fact, it is essential to refer to a 2018 European Commission report [ 7 ] on the costs of NOT having FAIR data.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, identification of multimorbidity patterns and polypharmacy correlation on the risk of mortality in elderly [ 5 ]. And second one, an early prediction service for 30-days readmission risk in patients with Chronic Obstructive Pulmonary Disease [ 6 ]. Concretely, the FAIR4Health platform included Privacy-Preserving Distributed Data Mining (PPDDM) methods to carry out a federated use of different AI algorithms, to identify association between de data (like the FP-Growth algorithm), and to perform predictions (like the Support Vector Machine, Logistic Regression, Decision Trees, Random Forest, Gradient Boosted Trees).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation